Effect Of Modified Cassava Flour (MOCAF) Substitution On The Physical And Sensory Quality Of Salt Bread - Nayla Sabrina; Cucu Cahyana; Sachriani Sachriani (Yayasan Riset dan Pengembangan Intelektual, 2026)
Salt bread is a Japanese-style bakery product characterized by a crisp outer crust, a soft crumb, and a savory butter flavor. Its quality depends strongly on the gluten network formed by wheat flour. This study evaluated the effect of modified cassava flour (MOCAF) substitution on the physical and sensory quality of salt bread. A completely randomized experimental design was used with three MOCAF substitution levels (10%, 20%, and 30%) and three replications. Bread volume was measured using the seed displacement method. Sensory quality was first validated by five expert panelists and then evaluated by 45 semi-trained panelists, with 15 evaluations per treatment. The assessed attributes included outer and inner color, MOCAF and butter aroma, MOCAF, butter, and salty taste, pore structure, outer-crust texture, and inner-crumb texture. Physical data were analyzed using one-way ANOVA followed by Duncan’s Multiple Range Test. In contrast, ordinal sensory data were analyzed using the Kruskal–Wallis test and pairwise follow-up testing at α = 0.05. MOCAF substitution significantly affected bread volume (F = 21.35), which decreased from 175.67 cm³ at 10% substitution to 162.00 cm³ at 20% and 127.33 cm³ at 30%. Sensory analysis showed significant differences in MOCAF taste (χ² = 8.00) and pore structure (χ² = 10.24), but no significant differences in color, aroma, butter, and salty taste, or outer and inner texture. The 10% MOCAF formulation most closely retained the expected volume, pore structure, flavor balance, crisp crust, and soft crumb of conventional salt bread. Therefore, 10% MOCAF substitution is recommended as the most appropriate formulation within the tested range.